Patient with suspected cauda equina syndrome - Metcalf-Cuenca, Gabriel (Cambridge University Press, 2025)
Cauda equina syndrome is the clinical syndrome seen when there is acute compression of the cauda equina nerve roots and is a rare neurosurgical emergency. The approximate incidence in patients presenting with low back pain is 0.27% but delays in investigation and treatment can result in life-changing permanent disability. The best practice for patients presenting with potential cauda equina syndrome is urgent MRI imaging at the presenting hospital to avoid delays in diagnosis. Patients with a positive finding of cauda equina compression should proceed to decompressive surgery to restore the diameter of the spinal canal urgently to reduce the risk of developing a permanent deficit.